Japan : Economic and Policy Developments. (IMF Staff Country Reports; Country Report, 2000)
Fiscal policy has been strongly expansionary for most of the past decade in Japan. The resulting strain on public finances has made stimulus policies more difficult to maintain. The stance of monetary policy has remained unchanged over the past year. Further progress in resolving banking problems is essential given the plan to remove blanket deposit insurance in April 2002 and to lay the foundation for sustained growth. The paper discusses recent developments in the field of structural reform and deregulation in Japan.